Pious Postmortems : Anatomy, Sanctity, and the Catholic Church in Early Modern Europe. - Bouley, Bradford (University of Pennsylvania Press, 2017)
In Pious Postmortems, Bradford A. Bouley considers the examinations performed on reputedly holy corpses in the sixteenth and seventeenth centuries at the request of the Catholic Church. Bouley concludes that neither religious nor scientific truths were self-evident but rather negotiated through a complex array of local and broader interests.